2023
DOI: 10.1002/osp4.690
|View full text |Cite
|
Sign up to set email alerts
|

Scaling a behavioral weight‐loss intervention for individuals with serious mental illness using the enhanced replicating effective programs framework: A preconditions phase proof‐of‐concept study

Abstract: BackgroundGiven the obesity's high prevalence among individuals with serious mental illness (SMI), translating weight‐loss interventions with demonstrated effectiveness is needed. This study describes the initial translation phase of such an intervention using the Enhanced Replicating Effective Programs (REP) Framework for delivery by mental health program staff.MethodsThe Achieving Healthy Lifestyles in Psychiatric Rehabilitation (Achieving Healthy Lifestyles in Psychiatric Rehabilitation) trial intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Given the prevalence of obesity among adults with SMI and its associated increased CVD risk, it is critical to implement effective behavioral weight loss interventions tailored to this population in real-world settings. The ACHIEVE trial demonstrated the efficacy and safety of such a behavioral weight loss intervention [ 11 ], which has been translated into the ACHIEVE-D weight management curriculum appropriate for delivery by community mental health center staff [ 16 ]. We are applying the Enhanced Replicating Effective Programs Framework to increase the acceptability and feasibility of implementing the ACHIEVE-D curriculum in community settings [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the prevalence of obesity among adults with SMI and its associated increased CVD risk, it is critical to implement effective behavioral weight loss interventions tailored to this population in real-world settings. The ACHIEVE trial demonstrated the efficacy and safety of such a behavioral weight loss intervention [ 11 ], which has been translated into the ACHIEVE-D weight management curriculum appropriate for delivery by community mental health center staff [ 16 ]. We are applying the Enhanced Replicating Effective Programs Framework to increase the acceptability and feasibility of implementing the ACHIEVE-D curriculum in community settings [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 outlines the components of the ACHIEVE-D curriculum, and Multimedia Appendix 2 includes a detailed description of the ACHIEVE-D curriculum. The curriculum has been previously tested in other studies [ 11 , 16 ]. As such, this study will focus on testing implementation interventions to support the delivery of the curriculum by community mental health program staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-conditions phase translated the ACHIEVE intervention into the ACHIEVE-Dissemination (ACHIEVE-D) program. 17,18 In brief, ACHIEVE-D is an adapted 6-month curriculum designed for delivery by mental health center staff, which has weekly, 45-min multi-purpose group sessions structured to include behavioral weight-management lessons and group exercise (26 modules over 6 months) as compared to the 18-month ACHIEVE intervention that included both individual and group sessions delivered by a trained interventionist. A non-randomized proof-ofconcept study was previously conducted at a single PRP in Maryland to determine the acceptability of ACHIEVE-D-study staff delivered the adapted curriculum to clients with SMI, which was observed by mental health center staff.…”
Section: Introductionmentioning
confidence: 99%
“…A non-randomized proof-ofconcept study was previously conducted at a single PRP in Maryland to determine the acceptability of ACHIEVE-D-study staff delivered the adapted curriculum to clients with SMI, which was observed by mental health center staff. 17 novel training and feedback strategies to address staff logistics and time constraints. 17 Whether performance coaching improved outcomes relative to the standard arm was also examined as a secondary outcome.…”
Section: Introductionmentioning
confidence: 99%